Notices (The Southern African Institute of Mining and Metallurgy)
ERRATA-AUTHOR'S REPLY IN SEPTEMBER, 1970, JOURNAL: PAGE 52 I. Left half of the page, 4th paragraph, fifth line from the bottom: for 22 / 5 1/2 %, read 22 / 5 1/2 %. 2. Right half of the page, fifth paragraph from the bottom, third line from the bottom: for N(l - p), read N(1 - p)x. 3. Right half of the page, fourth paragraph from the bottom, second line: for: at time t after time zero, read: at time x after time zero. NOTICE TO ALL STUDENT MEMBERS OF THE SOUTH AFRICAN INSTITUTE OF MINING AND METALLURGY The Institute offers each year for competition among Student Members of the Institute a prize, or prizes, should entries so warrant it, of up to the value of R100 to be awarded to the Student Member or Members who submit the best paper or dissertation on a topic appropriate to the interests of the Institute. In the case of Student Members who are in full time study at a university the dissertation or thesis which they may have to write in part fulfilment of their university curriculum may be accepted provided it is presented in a manner and on a topic suitable for publication in the Journal. The closing date for the receipt of papers shall be 31st December each year.